Luck or Rights? An Experiment on Preferences for Redistribution Following Inheritance of Opportunity - Warn N. Lekfuangfu; Nattavudh Powdthavee; Yohanes E. Riyanto (Institute of Labor Economics (IZA), 2022)
We experimentally investigate whether people generally perceive inheritance as effort-induced or luck-induced. By randomly matched two strangers in a lab setting, we test whether the sources of opportunity handed down from the 'testator' subjects determines later redistributive decisions among the 'heir' subjects. On average, redistribution is highest among the heirs whose chance of winning is determined by the pure luck of the paired testator. In contrast, our subjects treat inherited opportunity generated by effort of someone else who they are artificially linked with as relatively fair. Our results suggest that people would feel entitled to bequests and inheritance unless the randomness of inheritance has been made salient to them.
Keywords: D64; H2; 330; inheritance; fairness; redistribution; experiment; inequality of opportunity